Single-Frequency External Cavity Green Diode Laser - Yi-Hsi Chen; Wei-Chen Lin; Hong-Zhi Chen; Jow-Tsong Shy; Hsiang-Chen Chui (IEEE Photonics Journal)
We present a design of a single-frequency green InGaN external cavity diode laser (ECDL) with 40-mW output power and 10-MHz linewidth. The ECDL was mounted in the Littrow configuration, with an overall efficiency of approximately 52% and a tuning region of 8 nm. We analyzed the output efficiency of the ECDL under different polarization directions and emitted light patterns. We used a spectrometer to analyze the laser spectrum under the different applied currents and temperatures. Finally, we obtained the linewidth of the ECDL using a scanning Fabry–Perot interferometer and found that the linewidth varied with the wavelength.